Vesicovaginal Fistula Post Caesarean Hysterectomy - Maharjan, Manisha; Karki, Aruna; Dangal, Ganesh; Pradhan, Hema; Shrestha, Ranjana; Poudel, Rekha; Bajracharya, Nishma; Shrestha, Shreena; Tiwari, Kenusha Devi; Bharati, Sonu (Nepal Journal of Obstetrics and Gynaecology, 2020)
Genitourinary fistula is an abnormal communication between the urinary tract and genital tract, most common being the vesicovaginal fistula. In most of the cases fistula results mainly due to poor obstetric care in developing countries, where as in developed countries most of the urogenital fistulas are iatrogenic. It is mainly diagnosed by clinical examinations and intravesical dye test using methylene blue. Repair can be done via abdominal or vaginal route based on the findings. Here we present a case of 27 years postnatal mother referred to our centre with diagnosis of vesicovaginal fistula post cesarean hysterectomy that was repaired successfully via vaginal approach. Keywords: cesaerean hysterectomy, urinary leakage, vesicovaginal fistula